Development of Virtual Laboratory System Using EWB and Zoom Cloud in Dynamic Electricity Practicum as a Learning Solution in the Covid-19 Pandemic - I Gede Purwana Edi Saputra; Andri Estining Sejati; Nurazmi Nurazmi (Jurnal Pendidikan Fisika, 2021)
Covid-19 Pandemic has changed our education system, especially on practicum activity. This study aims at developing a virtual laboratory system using EWB and Zoom Cloud applications in a valid, practical and effective dynamic electricity practicum as a practical solution during the Covid-19 pandemic. The method used in this study is a modified Research and Development (RD) method consisting of identification of potential and problems, data collection, data for development, product design (draft I), validation, design revision, draft II, limited scale trial, product revision 1, draft III, broad-scale trial, product revision 2, and the final product. The trial sample in this study was class X students of SMK Negeri 2 Kendari in the Electrical Power Installation Engineering department the eligibility criteria with an internal consistency coefficient of 0.92 for the material and 0.84 for the media. After going through a validation test, the product developed is then tested on a limited and wide scale. From the results of trials on a limited scale, is was obtained that regarding the practicality value of the product 54.55% students’ responded “very support” and the rest 45.45% responded “support”, while in a large-scale trial of 77.50% students agreed on "very support” response, and 22.50% gave a “support” response. The effectiveness of the product is seen from the student's response and the classical completeness score where 100% of the students gained a practicum score of 75. Therefore, it can be concluded that Virtual Laboratory can be utilized as a learning solution during the COVID-19 pandemic at SMK Negeri 2 Kendari.